2005
DOI: 10.1116/1.1861044
|View full text |Cite
|
Sign up to set email alerts
|

Anion variations at semiconductor interfaces: ZnSe(100)/GaAs(100) superlattices

Abstract: Local interface composition and extended defect density in ZnSe/GaAs(001) and ZnSe/In 0.04 Ga 0.96 As (001) heterojunctions J.We extended our study of heterovalent interfaces between ZnSe͑100͒ and GaAs͑100͒ in superlattices using first-principles, density-functional theory calculations. Here, we concentrate on the changes in interfacial binding energy that occur when the stoichiometry is varied in the anion layer adjacent to the interface. This follows earlier work where the cation stoichiometry was varied. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In the structures A, B, C and D, the mixed interfaces are formed either by one Ga atom plus one Zn atom or by one Sb atom plus one Te atom. In another word, the stable mixed interfaces are constructed by 50% Sb and 50% Te atoms or by 50% Ga and 50% Zn atoms, as predicted by previous studies [19][20][21] , and there are two Ga-Te and two Zn-Sb "wrong bonds" at the interfaces. As we know, the Zn-Sb bond is an acceptor bond, providing 1/4 holes, and Ge-Te bond is a donor bond, providing 1/4 electrons.…”
Section: Resultsmentioning
confidence: 93%
“…In the structures A, B, C and D, the mixed interfaces are formed either by one Ga atom plus one Zn atom or by one Sb atom plus one Te atom. In another word, the stable mixed interfaces are constructed by 50% Sb and 50% Te atoms or by 50% Ga and 50% Zn atoms, as predicted by previous studies [19][20][21] , and there are two Ga-Te and two Zn-Sb "wrong bonds" at the interfaces. As we know, the Zn-Sb bond is an acceptor bond, providing 1/4 holes, and Ge-Te bond is a donor bond, providing 1/4 electrons.…”
Section: Resultsmentioning
confidence: 93%
“…Funato et al had investigated MOVPE growth procedures of GaAs/ZnSe heterostructures, the ZnSe-GaAs heterovalent quantum structures were fabricated, and their optical properties were characterized [3]. Farrell and LaViolette studied [4] three categories of simple heterojunctions that have links: (1) only As-Zn, (2) only Se-Ga, and (3) mixed As-Zn and Se-Ga bonds and more complex interface configurations, as well as various versions of interfacial stoichiometry [5]. He showed that the energy of the interface can be expressed as a simple sum of the energies of pairs with one bond, with an average error of less than 3%.…”
Section: Introductionmentioning
confidence: 99%